Independent effect of main components in particulate matter on DNA methylation and DNA methyltransferase: A molecular epidemiology study. (January 2020) - Wang, Yanhua; Wang, Ting; Xu, Mengmeng; Yu, Haitao; Ding, Chunguang; Wang, Zhenjie; Pan, Xingfu; Li, Yanbo; Niu, Yong; Yan, Ruixue; Song, Jiayang; Yan, Huifang; et al.
Highlights: Decrement of global DNA methylation presented in PM exposed population. Global DNA hypomethylation associated with elevated PAHs and Ni levels. Down-regulation of DNMT3B associated with elevated PM levels and PAHs component. Abstract: Background: There is a paucity of mechanistic information on the DNA methylation and particulate matter (PM) exposure. This study aimed to investigate the association of PM and its component with DNA methylation, and the roles of DNA methyltransferase ( DNMTs ). Methods: There were 240 high-exposed, 318 low-exposed and 210 non-exposed participants in this study. Individual concentrations of PM, polycyclic aromatic hydrocarbons (PAHs) and metals were identified by the monitoring data in their workplaces. Urinary 1-OHP and metals were determined as exposure markers. The global DNA methylation (% 5mC) and the mRNA expression of DNMT1, DNMT3A and DNMT3B were measured. We used mediation analysis to evaluate the role of DNMTs expression on DNA methylation alteration induced by PAHs and metals components. Results: The decreasing trend of % 5mC was associated with increment of PM exposure in all subjects. We found that one IQR increase in total PAHs (3.82 μg/m 3 ) and urinary 1-OHP (1.06 μmol/mol creatinine) were associated with a separate 6.08% and 7.26% decrease in % 5mC ( P = 0.009, P < 0.001), and one IQR increase in urinary Ni (27.75 μmol/mol creatinine) was associated with a 3.29% decrease in % 5mC ( P = 0.03). The interaction of urinary 1-OHP with Ni on global DNA methylation (%5mC) was not found ( P interaction = 0.89). PM exposure was significantly associated with decreased mRNA level of DNMT3B, but the mediated effect of the PAHs and Ni levels on % 5mC through the DNMT3B pathway was not observed. Conclusions: We found the decrement of global DNA methylation and DNMT3B expression with elevated PM levels in population. The independent mode of action on DNA hypomethylation was found from PAHs and metal components. Global DNA hypomethylation might be a potential biomarker for evaluation of adverse health effects in response to PM exposure.